6(2x-3)=20x+6

Simple and best practice solution for 6(2x-3)=20x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-3)=20x+6 equation:


Simplifying
6(2x + -3) = 20x + 6

Reorder the terms:
6(-3 + 2x) = 20x + 6
(-3 * 6 + 2x * 6) = 20x + 6
(-18 + 12x) = 20x + 6

Reorder the terms:
-18 + 12x = 6 + 20x

Solving
-18 + 12x = 6 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-18 + 12x + -20x = 6 + 20x + -20x

Combine like terms: 12x + -20x = -8x
-18 + -8x = 6 + 20x + -20x

Combine like terms: 20x + -20x = 0
-18 + -8x = 6 + 0
-18 + -8x = 6

Add '18' to each side of the equation.
-18 + 18 + -8x = 6 + 18

Combine like terms: -18 + 18 = 0
0 + -8x = 6 + 18
-8x = 6 + 18

Combine like terms: 6 + 18 = 24
-8x = 24

Divide each side by '-8'.
x = -3

Simplifying
x = -3

See similar equations:

| 7y+x=14 | | 8.6x-4=7.6x+5 | | 101325=x*9.82/0.1 | | xy-2x-4y=0 | | x^2=52 | | 3(5x+2)=7(x-3) | | 4x^2-2x^4+1=0 | | 2x^2-2x^4+1=0 | | 11-7x=159-35x | | 4p+3q=27 | | -37-4x=13-4x | | -1x-5x=5-7x | | 9a=9a+18a | | x+36=0 | | 96-4x=14x+22 | | 9x+13=5x+113 | | 6x+11=119-7x | | -2-2x=3x+11 | | 4x^2+49y^2-196=0 | | 5x+13=-23-7 | | 4x+39=4x+3 | | 6t^2=7t | | v^2+1=2v | | 2=3x+2x(x) | | x-10=5x+10 | | 2n-11=-3+6n | | c^2+9c=0 | | 3x-20=x+40 | | 2=x(2x+3) | | 5x+27=7x+4 | | 1.5(x+1.2y)+4(1.2x+1.2y)= | | (-4y-9z)(-2)= |

Equations solver categories